The Role of Regional Government in Providing Psychosocial Services for Women and Children Victims of Violence at the DP3AKB in Indramayu Regency - Cairoh; Ilham Setiawan; Mulyati Kartini (Diplomasi : Jurnal Demokrasi, Pemerintahan dan Pemberdayaan Masyarakat, 2025)
Violence against women and children in Indramayu regency continues to increase each year and has not been optimally addressed, despite the availability of government services through the DP3AKB. This study aims to evaluate the role of the local government in providing psychosocial services and to identify the challenges faced by DP3AKB Indramayu. Using a descriptive qualitative approach and Soerjono Soekanto’s theory, data were collected through interview, observation, and documentation involving informants from DP3AKB plays a significant role in delivering services such as counseling, psychosocial support, legal assistance, and social rehabilitation through the UPTD PPA, in collaboration with various sectors. However. Challenges include low reporting rates, limited budgets, and a shortage of professional staff such as psychologists. Strengthening resources and cross-sector collaboration is essential to optimize service delivery.